Monitoring interlaminar crack growth in ceramic matrix composites using electrical resistance. (15th March 2015) - Mansour, Rabih; Maillet, Emmanuel; Morscher, Gregory N.
Abstract : This letter introduces a method that uses electrical resistance to monitor crack growth during interlaminar fracture testing of woven SiC fiber-reinforced SiC matrix composites at room temperature without visual observation. The estimated crack length is in excellent agreement with the measured length after subtracting a constant value of resistance related to the initial stage of crack development. This non-visual monitoring method holds great promise for in situ measurement of crack growth during high-temperature testing of ceramic matrix composites.